Philosophy of Santri Alms as a Form of Response to Socio-Spiritual Gaps: Phenomenological Studies on the Concept of Altruism - Sri Wahyuni, Sandiani; Zahro Nur Latifah,; Kartika Anggraeni Sudiono Putri, (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
This study investigates the philosophy of "sedekah santri" (santri charity) as a response to socio-spiritual disparities in Indonesia. It highlights the ongoing spiritual crisis among many individuals who prioritize material wealth over genuine religious understanding. Through a phenomenological approach, the research examines how the Raudhatul Madinah Entrepreneurial Boarding School fosters altruistic values among its students. The study aims to explore the implementation of altruism within this context and its impact on addressing socio-spiritual gaps. Ultimately, the findings contribute to a deeper understanding of how spiritual practices can promote social responsibility and community support.